The results of a unique dietary supplement (nutraceutical formulation) used to treat the symptoms of long-haul COVID - Gaylis, Norman B.; Kreychman, Ida; Sagliani, Joanne; Mograbi, Josef; Gabet, Yankel (Frontiers in Nutrition, 2022)
Long-COVID is a syndrome characterized by debilitating symptoms that persist over 3 months after infection with the SARS-CoV-2 virus. It affects 15 to 33% of COVID-19 recovered patients and has no dedicated treatment. First, we found that β-caryophyllene and pregnenolone have a significant synergistic effect in the resolution of LPS-induced sepsis and inflammation in mice. Then we combined these two compounds with seven others and designed a unique dietary supplement formulation to alleviate long COVID inflammatory and neurological disorders. We performed a one-arm open-labeled study at a single site with 51 eligible patients from 18 states. Each participant recorded the severity level of 12 symptoms (including fatigue, weakness, cardiac and neurological symptoms, shortness of breath, gastrointestinal disorders, ageusia or anosmia, anxiety, joint pain, rash, cough, and insomnia) at baseline, 2-week, and 4-week time points. On average, all the symptoms were significantly milder after 2 weeks, with further improvement after 4 weeks. Importantly, each symptom was significantly attenuated in 72 to 84% of the participants. There were no significant adverse effects. Our data indicate that the use of this nutraceutical product is a safe and significantly efficient option to reduce multiple symptoms of long COVID.